The Influence of Work-Life Balance, Self-Efficacy, and Job Stress on Employee Performance at RSUD Rejang Lebong - agustian, Diaz; Nasution (Jurnal Manajemen, 2026)
The objective of this research was to investigate the influence of Work-Life Balance, Self-Efficacy, and Job Stress on employee performance within the Rejang Lebong Regional General Hospital. This study adopted a quantitative research design utilizing a survey questionnaire as the primary data collection instrument. Data were distributed directly to respondents in physical form and digitally via Google Forms. Multiple linear regression analysis was employed to analyze the data. The study’s population consisted of 620 employees engaged in health services and hospital administration. The random sampling technique was utilized, and the minimum sample size was determined using Hair’s formula, resulting in a total of 240 respondents. Data processing and analysis were conducted using SmartPLS software. The results indicate that Work-Life Balance demonstrates a significant positive effect on performance, suggesting that a better equilibrium between work and personal life is associated with increased employee performance. Self-Efficacy also exhibits a significant positive influence, as self-belief enables employees to complete tasks more effectively, demonstrate persistence, and adapt to pressure. Conversely, job stress has a significant negative effect, as high levels of stress resulting from workload and pressure reduce employee motivation, concentration, and performance effectiveness.